Validation and Uncertainty Estimation of an Ecofriendly and Stability-Indicating HPLC Method for Determination of Diltiazem in Pharmaceutical Preparations. (17th September 2013) - Sadeghi, Fahimeh; Navidpour, Latifeh; Bayat, Sima; Afshar, Minoo
Abstract : A green, simple, and stability-indicating RP-HPLC method was developed for the determination of diltiazem in topical preparations. The separation was based on a C18 analytical column using a mobile phase consisted of ethanol: phosphoric acid solution (pH = 2.5) (35 : 65, v/v). Column temperature was set at 50°C and quantitation was achieved with UV detection at 240 nm. In forced degradation studies, the drug was subjected to oxidation, hydrolysis, photolysis, and heat. The method was validated for specificity, selectivity, linearity, precision, accuracy, and robustness. The applied procedure was found to be linear in diltiazem concentration range of 0.5–50 μ g/mL (r 2 = 0.9996 ). Precision was evaluated by replicate analysis in which % relative standard deviation (RSD) values for areas were found below 2.0. The recoveries obtained (99.25%–101.66%) ensured the accuracy of the developed method. The degradation products as well as the pharmaceutical excipients were well resolved from the pure drug. The expanded uncertainty (5.63%) of the method was also estimated from method validation data. Accordingly, the proposed validated and sustainable procedure was proved to be suitable for routine analyzing and stability studies of diltiazem in pharmaceutical preparations.